Low dietary inclusion levels of Tenebrio molitor larva meal slightly modify growth performance, carcass and meat traits of Japanese quail (Coturnix japonica). (6th June 2022) - Secci, Giulia; Dabbou, Sihem; Lira de Medeiros, Adja Cristina; Addeo, Nicola F.; Atallah, Elie; Parisi, Giuliana; Moniello, Giuseppe; Bovera, Fulvia
Abstract: BACKGROUND: Insect‐derived proteins are a promising, valuable and permitted ingredient for poultry feed. However, more emphasis should be given to their effects on avian species different from chicken, such as quail ( Coturnix coturnix ), whose rearing represents an important activity. The present paper provides novel information about the impact of graded dietary levels of Tenebrio molitor (TM) larvae meal on quail growth and meat quality. RESULTS: Four diets were formulated with graded inclusion levels of TM, namely 1.65, 3.3 and 6.6 g on 100 g feed (T1.65, T3.3, T6.6, respectively) to partially replace the conventional proteins of a control diet (C). A total of 192 birds were allotted to one of the groups and fed for 35 days. The inclusion of TM meal linearly increased feed conversion ratio, and decreased carcass and breast weight. Texture and water holding capacity of meat were linearly reduced with increasing TM in diet, while fatty acid composition was not affected. However, the meat from quails fed diets including TM was subject to greater thermal damage than the C group; hence further studies are encouraged. CONCLUSION: TM meal inclusion at higher levels than 1.65% slightly impaired the growth performance of Japanese quails. Negligible effects on physical properties such as colour, texture, cooking loss and also on the fatty acid profile of the raw and cooked meat was found after including TM in quails' diet up to 3.3%. © 2022 Society of Chemical Industry.